Prevalencia de deficiencia de hierro y yodo, y parasitosis en niños de Arandas, Jalisco, México Prevalence of iron and iodine deficiency and parasitosis in children from Arandas, Jalisco, Mexico - Edgar Manuel Vásquez-Garibay; Enrique Romero-Velarde; Francisco Nápoles-Rodríguez; María Eugenia Nuño-Cosío; Francisco Trujillo-Contreras; Oscar Sánchez-Mercado (Instituto Nacional de Salud Pública, 2002)
Objetivo. Estimar la prevalencia de deficiencia de hierro, yodo y parasitosis en niños que asisten al Instituto Alteño para el Desarrollo de Jalisco (Inadej), Arandas, Jalisco, México. Material y métodos. Estudio transversal efectuado entre 1997 y 1999 con 432 niños de 12 a 120 meses de edad, de nuevo ingreso al Inadej. Se determinaron variables hematológicas, yodo en orina y presencia de parásitos. Se utilizaron las pruebas Ji cuadrada y t de Student en variables no paramétricas y paramétricas. Resultados. Hubo más anemia (20 vs 7.4% p=0.007) y deficiencia de hierro (60.9 vs 44.4% p=0.02) en prescolares que en escolares. El 29% presentaron deficiencia de yodo (10.5% moderada o grave) y 47.2% parasitosis. Predominaron G. lamblia y E. histolytica. Bajo salario, sexo masculino y no tener seguridad social se asociaron con parasitosis. Conclusiones. La elevada prevalencia de deficiencia de hierro, yodo y parasitosis obliga al sector salud estatal a ejecutar medidas eficaces para abatir estas enfermedades prevenibles. Objective. To estimate the prevalence of iron deficiency, iodine deficiency and parasitosis in children attending the Instituto Alteño para el Desarrollo de Jalisco ((Highlands Institute for Development of Jalisco State, INADEJ), Arandas, Jalisco, Mexico. Material and Methods. A cross-sectional study was conducted between 1997 and 1999, among 432 children aged 12 to 120 months attending the INADEJ. Measurements included hematological values, urine iodine concentration, and presence of parasites. Student's t test chi square tests were used for parametric and non-parametric analysis. Results. The prevalence figures of anemia (20 vs 7.4%, p=0.007) and iron deficiency (60.9 vs 44.4%, p=0.02) were higher in preschool than in school children. Iodine deficiency was found in 29% (10.5% moderate or severe) and parasitosis in 47.2% of children, mainly E. histolytica (30.2%) and G. lamblia (28.9%). Low income, male gender and lack of social security policy holding were associated to parasitosis. Conclusions. The high prevalence rates of iron deficiency, iodine deficiency, and parasitosis, should be addressed by state health services with effective interventions to restrain these preventable diseases.